RELIGIOUS WORLD OF TARAS SHEVCHENKO: CHRISTIAN SPIRITUALITY AND WORLDVIEW DOMINANT - Kyyak, C. R.; Genyk, L. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In this article the methods of comparative and retrospective analyzes outlook Taras Shevchenko, germenevtics and comparative approach in studies of his works and books of the Bible to understand that the world-famous Ukrainian poet had an orthodox Christian worldview, which was based on the biblical teaching; in relation to the commandments of God (the Decalogue) manifested his keen sense of justice that came from his mentality, but at the same time, the poet and the artist saw the world rulers of this departure from the Christian doctrine of the melee; so pay attention to the idea of ​national liberation movements, not only among the Ukrainians, but also among the other peoples of Europe and Asia, and encouraged them in all ways; by ideological views Shevchenko features can be attributed to religious and sacred, as he retained the respect not only to the traditional Christian view of the world, but also acknowledged the existence of small spiritual world, which was inherent in pre-Christian beliefs of the Slavic peoples. Taras Shevchenko left a priceless legacy artificial: sketches, drawings, watercolors and sepia, etchings, paintings, which gave hundreds of religious subjects and various architectural structures, some of whom died in the twentieth century, and modern scholars have come only in its unmatched images.